2010
DOI: 10.1007/s10571-010-9587-8
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin A and the Tumor Microenvironment

Abstract: Chromogranin A (CgA) is an acidic glycoprotein belonging to a family of regulated secretory proteins stored in the dense core granules of the adrenal medulla and of many other neuroendocrine cells and neurons. This protein is frequently used as a diagnostic and prognostic serum marker for a range of neuroendocrine tumors. Circulating CgA is also increased in patients with other diseases, including subpopulations of patients with non-neuroendocrine tumors, with important prognostic implications. A growing body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 49 publications
(63 reference statements)
1
45
0
1
Order By: Relevance
“…CgA is present in the serum of normal subjects at about 1 nmol/L levels (25). Higher circulating levels (in the nanomolar range) have been detected in patients with neuroendocrine tumors and in subpopulations of patients with breast cancer, prostate cancer, small and nonsmall cell lung cancer (11,(26)(27)(28), or in patients with heart failure, renal failure, hypertension, rheumatoid arthritis, giant cell arthritis, sepsis, and atrophic gastritis, or treated with proton pump inhibitors (9,25,26,29,30). Thus, the doses used in this study are biologically relevant as they are in the range of those found in patients with nonneuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CgA is present in the serum of normal subjects at about 1 nmol/L levels (25). Higher circulating levels (in the nanomolar range) have been detected in patients with neuroendocrine tumors and in subpopulations of patients with breast cancer, prostate cancer, small and nonsmall cell lung cancer (11,(26)(27)(28), or in patients with heart failure, renal failure, hypertension, rheumatoid arthritis, giant cell arthritis, sepsis, and atrophic gastritis, or treated with proton pump inhibitors (9,25,26,29,30). Thus, the doses used in this study are biologically relevant as they are in the range of those found in patients with nonneuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
“…CgA is released in circulation in normal subjects at about 1 nmol/L levels and in several pathologic conditions, including cancer, at higher levels in the nanomolar range (11). The CgA1-78 fragment, called vasostatin-1 (VS-1), can inhibit the formation of gaps in endothelial cell monolayers and the permeability to macromolecules induced by TNF-a, VEGF, and thrombin (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies showed that CgA is a good marker for diagnosis and prognosis of neuroendocrine tumors, even for monitoring their responses to chemotherapy (29,30,46), only few works have investigated the capability of baseline circulating CgA to predict the therapeutic response. Interestingly, in 3 studies carried out on SCLC, NSCLC, and prostate cancer, the response rates to chemotherapy inversely correlated with baseline CgA (37,47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of circulating CgA have been detected in patients with neuroendocrine tumors, in subpopulations of patients with prostate, breast or non-small cell lung cancer (NSCLC), and in patients with heart failure, renal failure, hypertension, rheumatoid arthritis, sepsis, hepatocellular carcinoma, liver cirrhosis, chronic hepatitis, pancreatitis, inflammatory bowel disease, or atrophic gastritis (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Furthermore, increased levels of CgA have been detected also in patients treated with proton pump inhibitors, a class of drugs commonly used to treat acid peptic disorders (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Well-established angiogenic growth factors, such as VEGF-A (Terris et al 1998) or angiopoietins (Srirajaskanthan et al 2009, Detjen et al 2010, are present in NETs. In addition, characteristic neuroendocrine secretion products, including chromogranin A fragments (Corti 2010) and serotonin (Asada et al 2009), affect angiogenesis and vascular permeability, altogether creating a unique stromal microenvironment.…”
Section: Introductionmentioning
confidence: 99%